PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS POTENSI LOKAL PEMBUATAN MINYAK NILAM (Pogostemon cablin Benth) DI KABUPATEN ACEH TAMIANG - Atiqah Zahra Ritonga; Syarifah Widya Ulfa; Lailatun Nur Kamalia Siregar (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
The development of biology learning modules based on local potential, especially the manufacture of patchouli oil (Pogostemon cablin Benth.) is certainly an interesting matter, at this stage the research was carried out in Aceh Tamiang with biodiversity material for class X SMA/MA. The study was carried out at SMAN 2 Patra Nusa, Manyak Payed, Aceh Tamiang from July 2021 to January 2022. This study uses the Borg & Gall model of research and development (R&D). The study tool consisted of a questionnaire sheet for material specialists, media professionals, educators, and students as well as a practicality test questionnaire. The study's test participants were students in class X-3 at SMAN 2 Patra Nusa, Manyak Payed, Aceh Tamiang. After the tryout was conducted on 30 students to ascertain their response to the module evaluation, a practicality test was also carried out to determine the practicality of the module for 10 students using a practicality test questionnaire instrument sheet. Based on the conclusions of the material expert validation, a percentage of 51.6% was attained with a respectable category. 90% of the validation results from media experts were extremely respectable. With a percentage of 94.7%, the teacher's response to the module yielded quite positive results. The module's results from student replies had a very respectable category percentage of 89.9%. The module's practicality test scores fell into the very practical category with a rating of 87.5%. Thus, both teachers and students can benefit from using the local potential based biology learning module on biodiversity content.